ORGANOMETRIC PARAMETERES OF LYMPH NODES STRUCTURES OF RATS IN DIFFERENT AGE GROUPS - Kashchenko, S.A.; Petizina, O.N. (World of Medicine and Biology, 2010)
The linear dimensions of lymph nodes of white outbred male rats (length, width, height and mass) in different age groups have been investigated. Quantitative changes of rats’ lymph nodes intestine depend on activity of immune system peripheral organs in different age periods.
Keywords: lymph nodes; immune system